The Effect Of Contingency Variables On Management Accounting System Characteristics And Managerial Performance - Muslichah, Muslichah (The International Journal of Accounting and Business Society, 2004)
A major strand of management accounting research has been the application of contingency theory to the analysis and design of management accounting systems. In particular, these studies have focused on the relationship between aspects of contingency variables on MAS characteristics and performance. This study examines (1) the role of decentralization on the relationship between contingency variables (information technology, strategy. environmental uncertainty, organizational interdependence) and management accounting system characteristics (2) the role of management accounting system characteristics on the relationship between contingency variables (information technology. strategy, environmental uncertainty. organizational interdependence and decentralization) and managerial performance. Management accounting system characteristics was deï¬ned on the extent to which managers use broad scope, timeliness, aggregation and integration MAS information for managerial decision making. Hypotheses were generated for both direct and indirect effects of contingency variables. The responses of 110 managers, drawn from manufacturing companies in East Java. were analyzed by using a structural equation modeling (SEM).